2019
DOI: 10.1039/c8en01089g
|View full text |Cite
|
Sign up to set email alerts
|

Plant species-dependent transformation and translocation of ceria nanoparticles

Abstract: Different plant species respond differently to nCeO2 under different culturing conditions: for some, deficiency of P enhances the accumulation of Ce (mainly Ce3+) and phytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
0
50
1
Order By: Relevance
“…This concentration affects plants physiology but it is not lethal for pea. In fact, majority of studies on toxicity of CeO 2 NPs to terrestrial plants use concentrations in the range 1-1000 mg/L −1 (Holden et al 2014;Rossi et al 2017b), while the phytotoxicity test as recommended by the Environmental Protection Agency, USA (Zhang et al 2019) approach the 2000 mg L −1 level. The fourth series was a reference treated with original Hoagland solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concentration affects plants physiology but it is not lethal for pea. In fact, majority of studies on toxicity of CeO 2 NPs to terrestrial plants use concentrations in the range 1-1000 mg/L −1 (Holden et al 2014;Rossi et al 2017b), while the phytotoxicity test as recommended by the Environmental Protection Agency, USA (Zhang et al 2019) approach the 2000 mg L −1 level. The fourth series was a reference treated with original Hoagland solution.…”
Section: Methodsmentioning
confidence: 99%
“…NPs approach plants through variety of mechanisms which are strongly dependent on their size, morphology, charge, settings and agglomeration (Pérez-de-Luque 2017; Yang et al 2017;Zhang et al 2019). All those factors affect the plant response and need to be carefully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the uptake of Cu(OH) 2 ENMs with higher solubility in roots of wheat (Triticum aestivum) is greater than those with lower solubility (e.g., CuO and CuS ENMs) after 1 h hydroponic exposure. [107] In a follow-up depuration study, the authors removed the exposure solutions an found that both CuO and CuS ENMs persisted in or on the roots and continued to release Cu for translocation to plant leaves over 48 h. There is also some indirect evidence from studies such as that by Zhang and coworkers; here, the authors reported that changing the plant culture medium, [108] plant species, [28] or morphology [26] of the CeO 2 ENMs affected analyte transformation and subsequent translocation. Importantly, removal of phosphates from the culture media dramatically enhanced Ce accumulation in the leaves.…”
Section: Effect Of Transformation On Root Uptake and Translocation Ofmentioning
confidence: 85%
“…Importantly, removal of phosphates from the culture media dramatically enhanced Ce accumulation in the leaves. [28] Rod-shaped CeO 2 ENMs have greater reactivity than other morphologies, including octahedral and cubical, and thus, have greater dissolution and accumulation in plant leaves. [26] Significantly higher amounts of CePO 4 needle-like clusters have also been observed on root surfaces ( Figure 2D).…”
Section: Effect Of Transformation On Root Uptake and Translocation Ofmentioning
confidence: 99%
See 1 more Smart Citation